A companion to the archaeology of the Roman Republic - Evans, Jane DeRose, 1956- (Chichester, West Sussex, UK : Wiley Blackwell, 2013)
The role of archaeology has expanded over the past 30 years, and research now frequently overlaps with the work of ancient historians and classicists. This book demonstrates how archaeological methods have been used to study the era of the Roman Republic, and the influences of non-Roman cultures on its formation. A collection of original essays by both emerging and established archaeologists with a wide range of nationalities and areas of interest, this book reveals how differing approaches and methodologies contribute to an understanding of the Republic across the Mediterranean basin. Of interest both to archaeologists themselves, and to students of ancient history, art history and classics, it offers a diverse approach to a fascinating field.
I. Material Culture and its Impact on Social Configuration -- II. Archaeology and the Landscape -- III. Archaeology and Ancient Technology -- IV. The Archaeology of Identity -- V. The Archaeology of Empire during the Republic -- VI. Republican Archaeology and the 21st Century.
"A John Wiley & Sons, Ltd., publication."
Includes bibliographical references and index.
Print version record.
Keywords: 510-30 B.C; Social archaeology -- Rome; Material culture -- Rome; Landscape archaeology -- Rome; Technology -- Social aspects -- Rome; Group identity -- Rome; Imperialism -- Social aspects -- Rome; HISTORY -- Ancient -- Rome; Antiquities; Group identity; Imperialism -- Social aspects; Landscape archaeology; Material culture; Social archaeology; Technology -- Social aspects; Rome -- History -- Republic, 510-265 B.C.; Rome -- History -- Republic, 265-30 B.C.; Rome -- Antiquities; Rome (Empire); Electronic books; History